Safety Protection of Under-passing Existing Rail Transit Structures Based on Midas GTS Finite Element Software - GU Zhangchuan (Chengshi guidao jiaotong yanjiu, 2025)
［Objective］ With the rapid expansion of urban rail transit networks, the intersection of multiple lines has become a common phenomenon in urban construction. In particular, the increasing cases of newly constructed tunnels using the mining method under-passing existing rail transit structures necessitate in-depth research on the safety protection of these structures. ［Method］ Based on the safety protection project of a city′s Rail Transit Line 8 mining method tunnel under-passing existing Rail Transit Line 3, Midas GTS finite element software is used to simulate the impact of different external working conditions on the upper part existing rail transit structure. Through a detailed analysis of the deformation characteristics of the existing rail transit structure under various construction procedures, as well as a comparative analysis of numerical simulation results and the on-site monitoring data, the construction impact on above-mentioned existing structures is explored. ［Result & Conclusion］ Numerical simulation results show that when the new Metro Line 8 using mining method for the under-passing tunnel construction, the deformations of the existing rail transit structure remain within the control indicators. The maximum horizontal displacement of the main structure is 0.54 mm, and the maximum upward deflection of vertical displacement is 1.92 mm. On-site measured data indicate that the maximum horizontal displacement of the existing rail transit main structure is 0.50 mm, and the maximum vertical displacement is 1.60 mm. This shows that under reasonable parameter selection, numerical simulation, as a safety risk assessment tool, provides simulation results in good agreement with actual measurements. Additionally, numerical simulation can accurately predict the most adversely affected positions and the extent of structural impact, providing significant guidance for on-site construction and monitoring.